Trends of HIV indicators in Egypt from 1990 to 2021: time-series analysis and forecast toward UNAIDS 90-90-90 targets - Ramy Mohamed Ghazy; Salah Al Awaidy; Sarah Hamed N. Taha (BMC, 2023)
Abstract Background Infection with Human immunodeficiency virus (HIV) and the development of acquired immunodeficiency syndrome (AIDS) pose severe threats to public health across the world. This study aimed to describe and forecast the trend of HIV indicators, including progress towards the 90-90-90 targets in Egypt since 1990. Methods The HIV indicators were graphically described, where the X axis is the time in a year and the Y axis is the value of the selected indicator for each year using data retrieved from UNAIDS. We used the Autoregressive Integrated Moving Average (ARIMA) model to forecast different HIV indicators from 2022 to 2024. Results Since 1990, HIV prevalence has been < 0.01, the number of people living with HIV (PLHIV) has increased from < 500 to 30,000 with a higher male predominance since 2010, and the number of children living with HIV has increased from < 100 to 1100. The number of pregnant women who needed antiretroviral treatment (ART) to prevent maternofetal HIV transmission increased from < 500 during 2010-2014 to 780 in 2021, the percentage of women who received ART increased from 3% in 2010 to 18% in 2021, the number of children exposed to HIV who did not get infection increased from < 100 in 1990-1991 to 4900 in 2021. The number of AIDS-related deaths increased from < 100 in 1990 to < 1000 in 2021. Based on forecasting, we expect that by 2024 the number of PLHIV will be 39,325(95%CI, 33,236-37,334), 22% (95%CI, 13.0%-32.0%) of pregnant females will have access to ART, 6100(95%CI, 5714-6485) HIV exposed children will not be infected, 77.0%(95% CI 66.0%-86.0%) of the population who knew their HIV status, and 71.0% (95%CI, 61.0%-81.0%) among those who know their HIV status will be on ART. Conclusion HIV is moving forward fast, however, the Egyptian health authority implements different control measures to control its spread.